The Role of Al-Hisba in Monitoring Weights and Measures (مجلة الواحات للبحوث والدراسات, 2026)
Al-Hisba" is a pivotal Islamic institution ensuring market justice through religious and civil oversight. The "Mohtasib" (market inspector) enforces the principle of "enjoining good and forbidding evil" by auditing weights and measures, preventing fraud, and protecting consumer rights. Beyond imposing Sharia-based penalties, this system fosters social and economic equilibrium. This regulatory role raises key questions regarding the standards, tools, and methodologies used to govern commercial transactions and eliminate exploitation in historical Islamic markets